2020
DOI: 10.1007/s10802-020-00664-1
|View full text |Cite
|
Sign up to set email alerts
|

Thinking about Others’ Minds: Mental State Inference in Boys with Conduct Problems and Callous-Unemotional Traits

Abstract: Children with conduct problems (CP) and high levels of callous-unemotional traits (CP/HCU) have been found to have an intact ability to represent other minds, however, they behave in ways that indicate a reduced propensity to consider other people’s thoughts and feelings. Here we report findings from three tasks assessing different aspects of mentalising in 81 boys aged 11–16 [Typically developing (TD) n = 27; CP/HCU n = 28; CP and low levels of callous-unemotional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…The ability to understand the thoughts of others and flexibility in taking another's perspective into account seems to be still developing in late adolescence and early adulthood ( 73 ). Plus, recent evidence suggests that, although adolescents with higher levels of CU traits do not seem to be less able than their peers to infer the thoughts of others, they seem to be less prone to take others' thoughts into account, at least in a spontaneous and effortless manner ( 74 ). This could explain why more lenient moral appraisals are observed in adolescents with higher levels of CU but not in adults with higher levels of psychopathic traits.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to understand the thoughts of others and flexibility in taking another's perspective into account seems to be still developing in late adolescence and early adulthood ( 73 ). Plus, recent evidence suggests that, although adolescents with higher levels of CU traits do not seem to be less able than their peers to infer the thoughts of others, they seem to be less prone to take others' thoughts into account, at least in a spontaneous and effortless manner ( 74 ). This could explain why more lenient moral appraisals are observed in adolescents with higher levels of CU but not in adults with higher levels of psychopathic traits.…”
Section: Discussionmentioning
confidence: 99%
“…Research using behavioral tasks shows a divergence between cognitive and affective subcomponents of cognitive empathy. Across studies, neither youth with CU nor adults with psychopathy showed neural differences or behavioral deficits in cognitive ToM, suggesting intact cognitive ToM in psychopathy (65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79). By contrast, the evidence regarding the relationship between affective perspective-taking/ToM and psychopathy is more mixed.…”
Section: Cognitive Empathy In the Psychopathic Subtypementioning
confidence: 97%
“…For the antisocial-only subtype, questionnaire-based evaluations of cognitive empathy suggested that these processes are intact (70,87). Similarly, when assessed behaviorally, several studies demonstrated that individuals in the antisocial-only subtype, across all developmental stages, exhibit intact cognitive empathy (68,75,76,(88)(89)(90). Though, admittedly examination of cognitive empathy in the antisocial-only subtype has been less systematic than research in the psychopathic subtype.…”
Section: Cognitive Empathy In the Antisocial-only Subtypementioning
confidence: 99%
See 2 more Smart Citations